EVALUASI KEBIJAKAN BADAN USAHA MILIK DESA (BUMDES) DILIHAT PADA TAHAP PELAKSANAAN (STUDI KASUS PADA BUMDES KARYA MANDIRI DI DESA KAPAR KECAMATAN MURUNG PUDAK KABUPATEN TABALONG) (JAPB, 2022)
One of the business units established by the village government to improve the economy of the village community is the Village Owned Enterprise. BUMDes is a breakthrough innovation for every village as an effort to increase PADes or Village Original Income. BUMDes management is fully carried out by the village community, namely from the village, by the village, and for the village. Efforts to increase the prosperity and welfare of the people require fair and balanced economic development, in order to increase the prosperity and welfare of the people from the village level so that villages do not only depend on the central government. This study aims to determine and analyze the Policy Evaluation of Village-Owned Enterprises (BUMDes) Karya Mandiri seen at the Implementation Stage (Case Study on BUMDes Karya Mandiri, Kapar Village, Murung Pudak Subdistrict, Tabalong Regency. This research uses qualitative methods with descriptive analysis. Descriptive research is research which aims to describe a character of a variable, group or social phenomenon that is currently happening in society Using the CIPP Evaluation Theory by Stufflebeam, namely: Context Evaluation (background evaluation), Input Evaluation (identification of human resource capabilities, tools, and costs), Process Evaluation (identification of the obstacles to program implementation), Product Evaluation (identification of the results of program implementation).The data used in this research are primary data and secondary data.The data analysis technique used in this research is mo data analysis technique. Miles and Huberman's interactive del which includes data reduction, display, and conclusion drowing or verification. The results of the study show that the Policy Evaluation of Village-Owned Enterprises (BUMDes) Karya Mandiri seen at the Implementation Stage (Case Study on BUMDes Karya Mandiri Kapar Village, Murung Pudak Subdistrict, Tabalong Regency is categorized as Not Successful. Keywords: Evaluation, Policy, BUMDes